Implementasi Kasih Kristus Sebagai Dasar Hidup Dalam Keluarga Kristen Berdasarkan Efesus 5:22 - 6:3 Di Kalangan Jemaat El- Shadday Gereja Pantekosta Di Indonesia Wamena Kota Kabupaten Jayawijaya - Tanrobak, Anike; Suparti, Hana; Uriptiningsih, Ana Lestari (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Today, many Christian families face a variety of problems, which are problems within the family that affect all aspects of life, such as the economy, education, health, children's problems, and various other problems that arise in daily life. Families experiencing problems in their lives often divorce, with obvious consequences for all family members. The absence of Christ's honour and love in a family, even if they are Christians, will cause wounds to their husbands, wives, and children. The Christian family is truly populated by sinners. However, these households are also places where family members recognise that they are sinners and understand the problems that will arise as a result of their sin. It takes realisation that the Christian family needs God to intervene in its household and prevent problems from disrupting their harmony, which will ultimately result in losing Christ. It is imperative to involve God in the household that God has joined together so that families who face problems every day can resolve them according to the truth of God's Word and restore their family harmony.